Optimization of Biscuit from Pedada Fruit and Purple Sweet Potato Flour - Jariyah; Ulya Sarofa; Nurul Absyah Wahyuningtyas (Nusantara Science and Technology Proceedings)
Biscuits are foods made from wheat flour with the addition of other food ingredients. It is made through the process of heating and printing. The characteristics of biscuits are generally determined by their crisp texture. One of its ingredients is Pedada fruit flour (PFF) which has high dietary fiber content. It serves as a complement when added to purple sweet potato (PSP) flour with a high source of anthocyanin and antioxidants. The purpose of this study is to optimize the effect of the proportion between PFF and PSP flour on product quality. The research method used was the Response Surface Methodology (RSM) code. The experimental level values were: +1,414(17.5:100); +1(15:95); 0(10:90); -1(5:85); and -1,414(2.5:80). Furthermore, the research designs between PSP flour to PFF were: (85:5); (95:5); (85:15); (95:15); (90:10); (90:10); (90:10); (90:10); (90:10); (90:2.5); (90:17.5); (80:10); and (100: 10). The data obtained were analyzed using the Expert Design 10.0 analysis. The results showed that the best treatment was in the proportion of PFF to PSP flour having a value of (90:10). This produced biscuits with criteria of: 6.18% of moisture; 2.63% of ash; 0.87% of fat; 3.26% of protein; 2.15% of crude fiber; 1.65% of antioxidant; breaking strength 7.43N; color L*34.0; color a*17.4; and color b*10.8. The optimum solution table obtained was level 2.5, and 99.88 for PFF and PSP flour respectively.